Assessment and evaluation of the transfer and dissemination of ITDI Styro-Plastic Densifier Technology - Villamor, Francis E.; Posadas, Roger (Quezon City University of the Philippines Diliman, Technology Management Center, 2014)
The Philippines has experienced problems on waste disposal despite the fact that there were already existing laws on proper management of solid wastes in the country. Generally, the increasing volume of solid wastes was indeed the result equally growing population of the country. On the other hand, new technologies to make life easier emerged as the years passed by. This parallel growth has provided the country both benefits and problems. The benefits are of course convenience that the new technology has brought to the people. Among these new technologies are the emergence of light and easy to dispose packaging materials such as plastics and Styropor. Although these technologies provided convenience to the people, it as well generated another problem which is the increasing volume of solid waste not only in dumpsites but also in the rural areas. About 40 percent of the total solid wastes in the country are plastics and Styropor while the rest are biodegradable wastes. While the biodegradable wastes are easy to decompose, the plastics and Styropor would take million years to decompose. This has been the reason why waste plastics and Styropor are increasingly deposited in the areas where they were actually disposed. This problem is noticeable especially in Metropolitan Manila area where flooding has been the main problem during rainy seasons. Flooding is mainly caused by these non-biodegradable wastes clogged into the city's drainage system. In order to address this issue, the Philippine government enacted the Republic Act 9003 also known as The Ecological Solid Waste Management Act 9003 also known as The Ecological Solid Waste Management Act of 2000 which otherwise created the National Solid Waste Management Council (NSWMC) as policy-making body and technical support providers. The Department of Science and Technology (DOST) being one of the active members of NSWMC had taken initiatives, through its research and development institutes, to develop technologies for recycling these biodegradable wastes as well as non-biodegradable wastes. The Industrial Technology Development Institute (ITDI) of the Department of Science and Technology (DOST) was able to developed more than two (2) technologies for biodegradable wastes which includes agricultural wastes (biomass). The other technologies were intended for recycling/reuse of waste plastics and Styropor into functional products. These technologies include Processes of Mixing Plastics into Asphalt Aggregates and the Process of Melting Wastes Plastics and Styropor to increase its density and transform into usable products. The latter is commonly called Densifier and will be the subject of our evaluation.
The Styro-Plastic Densifier Technology (for oftentimes referred to as the Densifier) was developed by the Materials Science Division (MSD) of ITDI and granted by the Intellectual Property Office (IPOPHL) a Utility Model Registration as process technology. It was transferred to local fabricators, who have undergone and passed the accreditation process, via a licensing agreement called the Memorandum of Agreement (MOA). The technology had gained so much popularity and in fact recognized by various awards-giving bodies. The MOA authorizes the Accredited Fabricators to fabricate and commercialize the technology while the technology was being disseminated to the rest of the country through DOST Regional and Provincial Offices. Initially, its impact had been evident in the reduction of plastic wastes and as income generator to some dumpsite workers. However, the profit that the end-product generated was quite low making the technology not suitable for business operation in an end-user level. However, the profit is significantly in the manufacturing level (fabricators). On the other hand, the technology generated some problems in the technical as well as the non-technical aspects. These problems affected the transfer and dissemination of the technology and both parties involved. There were initiatives undertaken but have not totally addressed most of the issues. Besides, the Republic Act 10055 also known as Philippine Technology Transfer Act of 2009 was approved about five (5) years after the start of the commercialization of the technology. This urged the concerned parties to review specific elements and components of the system but those initiatives were more focused on the technical aspects rather than all components of the system including the laws, policies and procedures governing the process and how do they affect each other. Having seen the issues, I decided to include the technology in list of selected topics for my special paper. Additionally, it was one of the most discussed technologies in the regions and was recommended by my former boss. The scope of this paper covers things associated with the transfer and dissemination of Densifier Technology, identify and evaluate areas having technical and legal concerns, and lastly, provide recommendations and conclusions.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Waste management -- method; Styro-plastic densifier technology